Th17 Inflammation Model of Oropharyngeal Candidiasis in Immunodeficient Mice - Bhaskaran, Natarajan (J Vis Exp, 2015)
Oropharyngeal Candidiasis (OPC) disease is caused not only due to the lack of host immune resistance, but also the absence of appropriate regulation of infection-induced immunopathology. Although Th17 cells are implicated in antifungal defense, their role in immunopathology is unclear. This study presents a method for establishing oral Th17 immunopathology associated with oral candidal infection in immunodeficient mice. The method is based on reconstituting lymphopenic mice with in vitro cultured Th17 cells, followed by oral infection with Candida albicans (C. albicans). Results show that unrestrained Th17 cells result in inflammation and pathology, and is associated with several measurable read-outs including weight loss, pro-inflammatory cytokine production, tongue histopathology and mortality, showing that this model may be valuable in studying OPC immunopathology. Adoptive transfer of regulatory cells (T(regs)) controls and reduces the inflammatory response, showing that this model can be used to test new strategies to counteract oral inflammation. This model may also be applicable in studying oral Th17 immunopathology in general in the context of other oral diseases.